Strategy dynamics: Agency, path dependency, and self‐organized emergence - Thietart, Raymond‐Alain (Strategic Management Journal, 2016)
Analysis of a 42‐year strategic journey at a large multinational firm exposes the dynamics behind its strategic evolution. Grounded on a complexity science paradigm, this article challenges our understanding of the role of agency in strategic timing while adding conceptual and methodological innovations. Based on micro and macro approaches, qualitative interpretations, and econometric studies, the results tend to show that while agency partly produces strategy dynamics and timing of actions, strategic evolution (when not random) is largely emergent and driven by its past. These findings move the understanding of strategic evolution and timing away from a strategic choice perspective and toward a complex combination of agency, causal determinism, and self‐organization. Copyright © 2015 John Wiley & Sons, Ltd.